Investigating students' physiological learning styles of studying literature in using interactive cd-rom among form four students in SMK Lundu - Rosnani, binti Saini. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study aims to identify the students' Physiological Learning Style Preferences among fonn four students in SMK Lundu in learning literature using Interactive CD-ROM (ICDR). It is also to find out whether there are any similarities or differences in learning literature using ICDR and without using ICDR. There were (n=253) two hundred and fifty-two students (151 Female, 102 males) of form four students from eight classes. The data was obtained through self-reporting questionnaire which was adapted from Reid's (1987) perceptual learning style Self-Reporting Questionnaire. Descriptive statistics in the fonn oftables were used to explain the data collected from the questionnaire. A pilot test was first carried out for the instrument to determine the validity and the reliability of the questionnaire. The findings revealed that there were not many differences between learning literature using ICDR and without ICDR which reflected the students' physiological learning style. The findings showed that the audio learning style preference and visual learning style preference both were minor learning style preference among fonn four students in learning literature using ICDR. In this study, recommendations are made to the future researchers to broaden their studies.